SISTEM INFORMASI KOPERASI MULYA ABADI SENTOSA KAMPUNG WATES KECAMATAN BUMI RATU NUBAN KABUPATEN LAMPUNG TENGAH PROVINSI LAMPUNG BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER 3 - Anie Rose Irawati; Wartariyus Wartariyus; Rico Andrian; Ananto Danu Prasetyo (Jurnal Pepadun, 2022)
Mulya Abadi Sentosa Cooperative processing data into information is still done manually where all member data along with existing transactions are recorded using books and Microsoft Excel, therefore there are often some obstacles encountered, an information system that can process all data in cooperatives is needed to become a cooperative. solutions in all existing constraints and shortcomings so that data processing can be integrated with the database so that it can solve problems. How to design and manufacture an information system that is suitable for the Mulya Abadi Sentosa Cooperative, and can assist the processing of transaction data in the cooperative. There are two admin users and members who can access the system and then later can manage member data and transactions so that the presentation of information can be managed easily. With this information system, it can help increase the speed of the reporting process in cooperatives.